Forecasting investment processes in airlines - Sadvakassova, K.G.; Abenova, M.; Moneva, I.; Mukhanova, G.K.; Zharasbayeva, A.Zh. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Object: The object of the article is to study the modeling of investment processes on the example of airlines. Methods: Systematic approach, the methods of scientific knowledge, induction, deduction, comparison, statistics, comparability, financial analysis, mathematical modeling, analysis and forecasting. Results: The financial risk of the considered airline project is mainly related to the prices for aircraft maintenance services, which are at low limits. The severity of the consequences of this risk is critical and there is a high probability of these events. From the risk analysis, it can be concluded that the most likely financial risk is the one that can suffer the most damage. Air Astana JSC needs to use the proposed risk analysis to form a judgment about the possible conse-quences and probabilities of investment project risks. Based on the research of investment processes in airlines, recom-mendations were formulated in the field of investment project evaluation. Conclusions: Based on the analysis of the investment activity of the Kazakh company, it was revealed that outdat-ed methods of evaluating the effectiveness of investment projects are used and it was proposed to use quantitative risk analysis and break-even assessment of the airline’s investment projects for this purpose. Despite the difficulties, avia-tion financing is an opportunity for new participants to get attractive returns, provided that the asset type and timing are chosen correctly. Based on the calculations, the inefficiency of the investment activity of the proposed Kazakh airline was revealed. The proposed methodology for calculating the break-even boundaries of investment projects will help improve the efficiency of investments
Авиакомпанияларда инвестициялық процестерді болжау
Прогнозирование инвестиционных процессов в авиакомпаниях
Keywords: investment; investment project; modeling; performance evaluation; break-even analysis; risk analysis; forecasting investment processes; airline economy